Elastic-plastic property evaluation using a nearly flat instrumented indenter. (1st January 2017) - Midawi, A.R.H.; Simha, C.H.M.; Gesing, M.A.; Gerlich, A.P.
Abstract: A 100-µm diameter, nearly flat, instrumented, indenter is used to indent aluminum AA-6463 and X80 pipeline steel. In contrast to sharp and spherical indenters, a rising load-displacement response is followed by a concave-downwards response during indentation. The substrate materials are characterized using tension and compression tests. Yield strengths measured under compression are within +/− 10% of the tensile values thereby providing partial support for assuming symmetric tension-compression response. Based on imaging of the actual indenter using a Scanning Electron Microscope, a model of the indenter that accounts for the curved contact profile was created, assumed to be rigid and used in the finite element simulations. In the simulations, tensile yield strength and flow properties, obtained by tensile testing are used to describe the behavior of the substrate and good agreement with measured indentation force-displacement curves was obtained when the exact shape of the indenter was used. The agreement is poor when the contact profile of the indenter was idealized as flat. In the context of the inverse approach, using the Efficient Global Optimization technique, fits to the stress-strain curves of both of the alloys were obtained, and again the curvature of the indenter contact profile is found to be crucial. This work sets the stage for a large-scale deployment of the inverse approach to map the stress-strain response of heterogeneous microstructures such as welds.